Arbitration in Air Cargo Transport Contracts: Between International Conventions and National Legislation - Alkhawaldeh, Mohammad Naser Abdul Karim (Indian Journal of Information Sources and Services, 2025)
This study aimed considering the growing trends in the air cargo transport sector—to provide a concise summary of international arbitration’s development as a workable substitute for resolving disputes arising from air cargo transport contracts. It also highlighted the innovative provisions introduced by international conventions regulating air arbitration, which differ from traditional arbitration rules. Based on this analysis, the study reached several conclusions and recommendations. The key findings indicated that arbitration in air transport disputes is inherently judicial arbitration, as it relies on strict legal rules under the Montreal Convention. Consequently, the relevant international conventions (Montreal and Warsaw) imply that arbitration in this field is limited to judicial arbitration, excluding amicable arbitration (conciliation), reflecting a clear trend toward restricting parties’ autonomy in arbitration agreements within air transport. The primary recommendation was the necessity to amend Jordanian legislation governing air cargo transport contracts and the Jordanian Arbitration Law by introducing specialized provisions for air cargo disputes and their arbitration mechanisms, as these are now essential for protecting affected parties.